Grazing led to an increase in the root: shoot ratio and a shallow root system in an alpine meadow of the Tibetan plateau - Wang, Duobin; Ding, Wenqiang (Frontiers in Environmental Science, 2024)
Grazing is a main land use of natural grasslands in the world, which has both positive and negative impact on plant community structure and ecosystem functioning. However, the effects of long-term grazing management on the plant–soil system, in particular above- and belowground community characteristics, are still not well understood in alpine meadow community. In this study, we investigated the vegetation, roots, and soil properties under three management types (16 years of fencing since 2004-2020, moderate grazing and heavy grazing managements) in an alpine meadow on the Tibetan Plateau. The results showed that, compared with moderate grazing meadows, long-term fencing increased plant community cover, above- and belowground biomass, proportion of grass and litter but reduced forbs and soil bulk density, which caused the increases in soil organic carbon, total nitrogen and water content and the decreases in soil pH. However, heavy grazing led to opposite changes in proportion of grass, community biomass and soil physicochemical properties. The maximum of species richness and plant density appeared in moderate grazing meadows, supporting the intermediate disturbance hypothesis, and it can maintain above- and belowground biomass and soil physicochemical properties at medium level. Grazing increased the root: shoot ratio and caused root system shallow, which is consistent with the optimal partitioning hypothesis. Overall, our study suggested that moderate grazing is a more reasonable grazing management for sustainable development in alpine meadows of Tibetan Plateau, fencing could be an effective management strategy for vegetation restoration as well as for nutrient sequestration in degraded grasslands, but long-term fencing dose not benefit for biodiversity maintenance.